BRD4 promotes glioma cell stemness via enhancing miR‐142‐5p‐mediated activation of Wnt/β‐catenin signaling. Issue 3 (14th November 2019) - Wang, Jubo; Quan, Yu; Lv, Jian; Gong, Shouping; Dong, Danfeng
Abstract: The bromodomain protein BRD4 exerts carcinogenic effects in many cancers. However, its roles in glioma occurrence are still confused. Here, it is found that BRD4 expression is increased in glioma tissues and negatively correlated with the overall survival of glioma patients. We construct cellular experiments indicating that BRD4 promotes glioma cell stemness by analyzing ALDH1 activity, master stemness regulator expression, and sphere formation ability. Mechanistically, BRD4 knockdown triggers a switch of miR‐142‐5p promoter methylation, which targets Wnt3a and thus further inactivates Wnt/β‐catenin signaling. Importantly, inhibition of miR‐142‐5p or reactivation of Wnt/β‐catenin signaling rescues the inhibition of BRD4 knockdown on glioma cell stemness. As a result, these results not only indicate an unforeseen connection between BRD4, miR‐142‐5p, and Wnt/β‐catenin signaling, but also reveal a promising epigenetic‐based therapeutic strategy that might be explored for glioma patients.